2018
DOI: 10.3906/sag-1708-54
|View full text |Cite
|
Sign up to set email alerts
|

Soft spot: the important zone at the standard posterior portal of shoulder arthroscopy

Abstract: Background/aim: The localization of the standard posterior portal of shoulder arthroscopy and landmarks mentioned in the literature are unclear. The purpose of this prospective cadaveric study was to determine the localization of the standard posterior portal and its distance to the neural structures. Materials and methods:One fresh frozen and 10 formalin-fixed adult cadaveric shoulders were dissected. In the beach chair position, a 5-mm trocar was placed anteroposteriorly from the superior edge of the subscap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Использовали стандартную 30° оптику и стандартное оборудование для артроскопии крупных суставов. Доступ в полость сустава начинали с установки стандартного заднего порта в области «мягкой точки» [13]. Производили диагностическую артроскопию плечевого сустава с оценкой внутрисуставных структур (рис.…”
Section: хирургическая техника комбинированного эндоскопического вмеш...unclassified
“…Использовали стандартную 30° оптику и стандартное оборудование для артроскопии крупных суставов. Доступ в полость сустава начинали с установки стандартного заднего порта в области «мягкой точки» [13]. Производили диагностическую артроскопию плечевого сустава с оценкой внутрисуставных структур (рис.…”
Section: хирургическая техника комбинированного эндоскопического вмеш...unclassified
“…Little research has been performed assessing the best site for portal placement. Most research is based on small volume cadaveric studies, anecdotal evidence and surgeon preference [2][3][4][5][6]8 .…”
Section: Level Of Evidence: Level IImentioning
confidence: 99%
“…There are many portal placement options described in the literature [2][3][4][8][9] , but the posterior portal is the most commonly described. The posterior portal is traditionally introduced at a point relative to the posterior corner of the acromion (PCA) through J o u r n a l P r e -p r o o f an area referred to as the "soft spot" which has now been identified as a triangular fibrocartilaginous area between the deltoid heads 6 . More recent research has shown that using the PCA as a reference point has its own limitations due to the variability of the anatomy in this region 5,6 , yet is still remains the standard of care across many institutions.…”
Section: Level Of Evidence: Level IImentioning
confidence: 99%
See 2 more Smart Citations